2006
DOI: 10.1206/0003-0090(2006)299[1:psodfa]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Systematics of Dart-Poison Frogs and Their Relatives (Amphibia: Athesphatanura: Dendrobatidae)

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

38
777
9
52

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 531 publications
(876 citation statements)
references
References 289 publications
38
777
9
52
Order By: Relevance
“…The resulting phylogenetic tree (Figure 1) shows that A. baeobatrachus and Mannophryne trinitatis, which belong to the family Aromobatidae, form a strongly supported clade. This clade is the sister group of Dendrobatidae, which is in accordance with previous studies (Grant et al 2006). Given several species within this genus might face decline or might already have gone extinct (Courtois et al 2015;Fouquet et al 2015), resolving taxonomic uncertainties is crucial to assess conservation priorities.…”
supporting
confidence: 88%
“…The resulting phylogenetic tree (Figure 1) shows that A. baeobatrachus and Mannophryne trinitatis, which belong to the family Aromobatidae, form a strongly supported clade. This clade is the sister group of Dendrobatidae, which is in accordance with previous studies (Grant et al 2006). Given several species within this genus might face decline or might already have gone extinct (Courtois et al 2015;Fouquet et al 2015), resolving taxonomic uncertainties is crucial to assess conservation priorities.…”
supporting
confidence: 88%
“…La mayoría de secuencias provienen de Summers et al (1999), Clough & Summers (2000), Santos et al (2003), Symula et al (2003), Grant et al (2006), Noonan & Wray (2006), Roberts et al (2006), Brown et al (2008), Santos et al (2009) y Brown et al (2011. Los números de acceso al GenBank están listados en la Fig.…”
Section: Análisis Filogenéticounclassified
“…Grant et al (2006) ubicaron a estas ranas en la superfamilia Dendrobatoidea, la misma que se subdivide en las familias Aromobatidae y Dendrobatidae. Según Ron et al (2011), en el Ecuador se registran dos géneros y ocho especies para Aromobatidae (Allobatinae y Anomaloglossinae) y a Dendrobatidae (Colostethinae, Dendrobatinae e Hyloxalinae) pertenecen 45 especies de 8 géneros (Ameerega, Andinobates, Colostethus, Epipedobates, Excidobates, Hyloxalus, Oophaga y Ranitomeya).…”
Section: Introductionunclassified
“…Poelman (2006) provided a wellfounded critique on the splitting of Dendrobates into four genera that only can be separated on the basis of molecular data. Santos et al (2009) did not accept the split of Dendrobates as proposed by Grant et al (2006) and again considered Adelphobates (and other genera proposed by Grant et al [2006]) part of Dendrobates. Rodrigues et al (2011) In the present paper we provide a detailed description of the range of Dendrobates galactonotus and its known color morphs, describe the color morphs known in nature, provide information about its habitat and deal with the potential threats to the species.…”
Section: Introductionmentioning
confidence: 94%
“…Vences et al (2003) found molecular differences between D. galactonotus and other large species of Dendrobates, and found that genetically it was closer to some small Amazonian poison frogs like D. castaneoticus Caldwell andMyers, 1990 (Lötters 2003), but these authors took a prudent position about this surprising find ("it should be interpreted cautiously until more sequence data for this species become available"), and did not make any nomenclatural changes. Grant et al (2006), based on molecular data only, erected the genus Adelphobates for D. galactonotus, the sympatric, much smaller D. castaneoticus, and two other small species, although from several comments it is clear they realized the discrepancy between the results of molecular and morphological character data ("…the occurrence of galactonotus in this clade is unexpected, as its morphology shares little with the diminutive castaneoticus and quinquevittatus") within this new genus. Poelman (2006) provided a wellfounded critique on the splitting of Dendrobates into four genera that only can be separated on the basis of molecular data.…”
Section: Introductionmentioning
confidence: 95%